Judentum und Arbeiterbewegung Das Ringen um Emanzipation in der ersten Hälfte des 20. Jahrhunderts - Börner, Markus; Jungfer, Anja; Stürmann, Jakob (Europäisch-jüdische Studien - Beiträge, 2018)
Before the Second World War, individuals of Jewish origin played a disproportionate part in the labor movement, which was a central current in the struggles for emancipation. Especially in Eastern Europe, there were Jewish labor organizations that fought a double battle against the oppression of the proletariat and the Jews. This volume examines their areas of activity, the role of anti-Semitism, and changing self-perceptions.